A full set of 8, 4′-oxy-8′-phenylneolignan stereoisomers from Sophora tonkinensis and their absolute configurations by TDDFT. (May 2022) - He, Hao-Ke; Li, Xin; Yang, Sheng-Li; Tian, Meng-Yin; Zhang, Qian-Ru; Zhang, Ning; Hou, Qi; Lin, Ming-Bao; Wang, Su-Juan
Abstract: A full set of 8, 4′-oxy-8′-phenylneolignans with four chiral carbons, named (+)/(−)-leptolepisols D1‒D2 and (+)/(−)-sophorols A‒F, were isolated from the roots and rhizomes of Sophora tonkinensis Gagnep., including 14 previously undescribed stereoisomers, along with 2 known leptolepisol D diastereomers. Their planar structures and relative configurations were elucidated by detailed spectroscopic analysis (HRESIMS and NMR). Based on a highly accurate conformer filtering protocol at low computational cost, the absolute configurations of full set 8, 4′-oxy-8′-phenylneolignans were completely assigned by TDDFT calculations of ECD spectra for the first time. Furthermore, (+)/(−)-sophorol A, (−)-sophorol B, and (−)-sophorol E could moderately suppress the lipopolysaccharide-induced nitric oxide production in murine macrophages at 10 μM, with inhibitory ratios of 48.4–52.9%. Graphical abstract: A full set of 8, 4′-oxy-8′-phenylneolignans with four chiral carbons were isolated from Sophora tonkinensis Gagnep. Four compounds could suppress the LPS-induced NO production in murine macrophages. Image 1 Highlights: Sixteen 8, 4′-oxy-8′-phenylneolignans were isolated, 14 of which were undescribed. The absolute configurations of 8, 4′-oxy-8′-phenylneolignans were assigned by TDDFT. An accurate conformer filtering protocol at low cost for flexible molecules was used. Four isomers exhibited moderately anti-inflammatory activities.